2005
DOI: 10.1038/sj.bjc.6602428
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor double targeting by a tyrosine kinase inhibitor (Iressa) and a monoclonal antibody (Cetuximab). Impact on cell growth and molecular factors

Abstract: Among the recent advances in the molecular targeted therapy of cancer, the applications focused on epidermal growth factor receptor (EGFR) are currently the most promising and the most advanced at clinical level. In view of the different modes of action of monoclonal antibodies and tyrosine kinase inhibitors (TKI), it is tempting to examine the effect of a combination between these two EGFR targeting approaches. It was the purpose of the present study to test this combination at experimental level by using two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 29 publications
2
24
1
2
Order By: Relevance
“…gefitinib, erlotinib) enhanced tumour growth inhibition over that observed with either agent alone (Huang et al, 2004;Matar et al, 2004). However, others have found that combination of cetuximab and gefitinib was antagonistic in all cell lines considered, suggesting that a double-hit strategy with Mabs and TKIs must be considered with caution (Fischel et al, 2005). Another strategy may be combination of EGFR antagonists (Mab or TKI) with inhibitors of RAS or phosphatidyl inositol-3 kinase pathways, which are downstream of the EGFR (e.g.…”
Section: Rash and Clinical Outcomementioning
confidence: 99%
“…gefitinib, erlotinib) enhanced tumour growth inhibition over that observed with either agent alone (Huang et al, 2004;Matar et al, 2004). However, others have found that combination of cetuximab and gefitinib was antagonistic in all cell lines considered, suggesting that a double-hit strategy with Mabs and TKIs must be considered with caution (Fischel et al, 2005). Another strategy may be combination of EGFR antagonists (Mab or TKI) with inhibitors of RAS or phosphatidyl inositol-3 kinase pathways, which are downstream of the EGFR (e.g.…”
Section: Rash and Clinical Outcomementioning
confidence: 99%
“…Indeed, in two recent studies, cotargeting of the EGFR with a combination of cetuximab and gefitinib or erlotinib was shown to be superior over the targeting of tumor cells with the single agent (25,26). More recently, the combination of cetuximab with gefitinib was reported to induce an antagonistic effect in EGFR-positive tumor cells (27).…”
Section: Introductionmentioning
confidence: 99%
“…The combined administration of exemestane and erlotinib reduced cell numbers in all cell lines examined in this study. However, inhibitor synergy was identified only in H23 cells according to a formula that Fischel et al (2005) previously described (Figure 1c, d, e).…”
Section: Resultsmentioning
confidence: 99%